2018
DOI: 10.1159/000487028
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of the MiR-17-92 MicroRNA Cluster in Germ Cells Causes Subfertility in Female Mice

Abstract: Background/Aims: Oogenesis is a highly complex process that is intricately regulated by interactions of multiple genes and signaling molecules. However, the underlying molecular mechanisms are poorly understood. There is emerging evidence that microRNAs contribute to oogenesis. Here, we aimed to investigate the role of miR-17-92 cluster in regulating oogenesis. Methods: The miR-17-92 cluster was genetically ablated in germ cells of female mice by applying the Cre-loxp system for conditional gene knockout. Mati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Moreover, miR-17-92 germ cell-specific KO female mice displayed a low fecundity with increased follicular atresia and reduced ovulation rate (Wang et al, 2018). All the above indicated the potential function of miR-17-5p in folliculogenesis.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Moreover, miR-17-92 germ cell-specific KO female mice displayed a low fecundity with increased follicular atresia and reduced ovulation rate (Wang et al, 2018). All the above indicated the potential function of miR-17-5p in folliculogenesis.…”
Section: Discussionmentioning
confidence: 77%
“…miR‐17‐5p was reported to be related to progression of ovarian cancers and endometrial cancer, and had essential roles in vital processes like cell cycle regulation, proliferation and apoptosis (Li et al, ; Shen et al, ). Moreover, miR‐17‐92 germ cell‐specific KO female mice displayed a low fecundity with increased follicular atresia and reduced ovulation rate (Wang et al, ). All the above indicated the potential function of miR‐17‐5p in folliculogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, studies have found that the imbalance of miR-423, miR-33b, and miR-142 may lead to polycystic ovary syndrome [ 17 ]. The deletion of the miR-17-92 cluster [ 18 ] and miR-7a2 [ 19 ] can lead to infertility in female mice. This suggests that miRNA might also affect the reproductive performance of female goats, thus affecting the economic effect of the goat industry.…”
Section: Introductionmentioning
confidence: 99%